2023
DOI: 10.1021/acs.jchemed.3c00685
|View full text |Cite
|
Sign up to set email alerts
|

Waste Iron Oxidation Reaction-Assisted Electrochemical Flocculation for Rhodamine B Extraction from Wastewater: A Hands-On Experiment for Undergraduates

Xiang Peng,
Baochai Xu,
Yujie Zeng
et al.

Abstract: Removing the pollutants from various wastewater is crucial to the environment, ecology, and humans. However, the pollutants are generally removed by chemical decomposition, which not only consumes a lot of energy but also produces carbon emissions. Electrochemical flocculation is effective to extract pollutant molecules and heavy ions from wastewater. To solidify the theoretical knowledge of electrochemical flocculation including electrochemistry and environmental science with industrial application, we propos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 32 publications
0
1
0
Order By: Relevance
“…Research has shown that RhB can induce toxicity in aquatic organisms, particularly at concentrations exceeding 1 mg/L (Skjolding et al, 2021). To address this issue, various techniques for removing this cationic dye have been proposed and implemented (Peng et al, 2024;Vosough et al, 2024), with adsorption being one prominent method. This approach has been cited in numerous recent studies as a costeffective, industrially feasible, promising, and efficient means of combating a spectrum of pollutants Kerrou et al, 2021), inclusive of RhB dye.…”
Section: Introductionmentioning
confidence: 99%
“…Research has shown that RhB can induce toxicity in aquatic organisms, particularly at concentrations exceeding 1 mg/L (Skjolding et al, 2021). To address this issue, various techniques for removing this cationic dye have been proposed and implemented (Peng et al, 2024;Vosough et al, 2024), with adsorption being one prominent method. This approach has been cited in numerous recent studies as a costeffective, industrially feasible, promising, and efficient means of combating a spectrum of pollutants Kerrou et al, 2021), inclusive of RhB dye.…”
Section: Introductionmentioning
confidence: 99%